AFFIRMING WIBU’S STEREOTYPES THROUGH YOUTUBE VIDEOS - Junianto, Iqbal Eka; Tambunan, Shuri Mariasih Gietty (International Review of Humanities Studies, 2024)
In 2022, based on Google Trends tools, Indonesia is ranked third as the country with the most searches related to Japanese anime. Wibu is a term that refers to someone who is outside Japan but likes and even tends to be obsessed with the culture of that country. This research aims explore how stereotypes of Wibu in Indonesia are constructed by digital media, specifically YouTube. Research findings show that Wibu in Indonesia is stereotyped as "smelling of onions", "Wibu Nolep", "perverted Wibu" and “pshycopath Wibu.” By conducting textual analysis on YouTube videos that are related to Wibu content, we argue that the construction of Indonesian Wibu’s stereotypes are done through narrative and visual elements in the videos. Based on this research, researchers discovered the role of YouTube in affirming the stereotypical construction of Wibu in Indonesia with ambiguous representations.